COMPARATIVE ANALYSIS OF ECONOMIC ORDER QUANTITY (EOQ) METHOD WITH JUST IN TIME (JIT) METHOD AS PLANNING AND CONTROLLING OF BATAKO RAW MATERIAL SUPPLY AT UD. ULINNUHA - Pifi Nuryani; Elmi Rakhma Aalin (State Islamic Institute (IAIN) Tulungagung, 2021)
The purpose of this study is to compare the planning and controlling of the supply of brick raw materials between the Economic Order Quantity (EOQ) method and the Just In Time (JIT) method at UD Ulinnuha. In addition, this study also purposes to determine which methods should be applied to UD Ulinnuha from both methods. Interviews, observations, and documentation are used to get data on purchase costs, usage, storage, and ordering of raw materials. The type of research used in this study is applied research. The results of this study indicate that both methods, both EOQ and JIT can work appropriately and optimally at UD Ulinnuha. But the two methods are not suitable if applied to UD Ulinnuha because if using the JIT method, the storage warehouse is inadequate to accommodate the raw material inventory. If using the EOQ method the warehouse can accommodate raw material inventory, but in real terms, the warehouse can`t accommodate raw materials according to the maximum inventory calculation results. So that the two methods are not recommended by researchers and are recommended to continue using company policies because company policies have taken into account the conditions in the field.